2006
DOI: 10.1093/jac/dkl348
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and plasma efavirenz concentrations in HIV-infected patients switching from successful protease inhibitor-based highly active antiretroviral therapy (HAART) to efavirenz-based HAART (SUSTIPHAR Study)

Abstract: For moderately pre-treated HIV-infected patients with few mutations who switched to efavirenz from previous successful HAART, the proposed plasma efficacy-threshold was reached without any dosage adaptation. VS was maintained beyond 12 months, despite high inter-patient and intra-patient variabilities of intracellular and plasma efavirenz concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…To our knowledge, two studies reported intracellular concentrations of raltegravir [2,3] where the results are consistent with ours. We also observed a low raltegravir intracellular PBMC accumulation (average 13% of plasma concentration) with a large variability in concentrations, probably reflecting variability in expression of cellular mechanisms (drug efflux, binding) and metabolizing enzymes, similarly to other antiretrovirals such as efavirenz [15] . This data was recently confirmed for raltegravir [3] .…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge, two studies reported intracellular concentrations of raltegravir [2,3] where the results are consistent with ours. We also observed a low raltegravir intracellular PBMC accumulation (average 13% of plasma concentration) with a large variability in concentrations, probably reflecting variability in expression of cellular mechanisms (drug efflux, binding) and metabolizing enzymes, similarly to other antiretrovirals such as efavirenz [15] . This data was recently confirmed for raltegravir [3] .…”
Section: Discussionsupporting
confidence: 76%
“…The endpoint concentration for resistance selection against the microbicide NNRTIs was set to 1,000 nM (roughly 329 ng/g), based on TMC120 tissue concentrations measured previously in the macaque model and for humans (46,61). The EFV resistance selection was also stopped at 1,000 nM, which was defined as a subtherapeutic concentration considering the expected EFV plasma levels of 1 to 4 mg/liter (18,49,56) in HIV-infected subjects. For NVP, the endpoint was set at 5,000 nM because NVP plasma levels range from 0.36 to 1.59 mg/liter 3 days after the receipt of a single-dose of 200 mg to prevent mother-to-child transmission (43).…”
Section: Antiretroviral Compoundsmentioning
confidence: 99%
“…This correlation was already reported for LPV [3] with a regression coefficient of 0.63 while for EFV, the published data are sometimes contradictory. Indeed, two studies reported a good correlation between CC and TPC with regression coefficients ranging between 0.77 and 0.58 [3,22], while another study failed to show such an association between intracellular and plasma concentrations [4].…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation could be that measuring plasma drug concentration is of limited clinical value because the major target of these drugs is within the infected cells and only the fraction reaching this intracellular compartment is expected to be active against HIV replication. In this respect, several studies have, however, shown a good correlation between intracellular and plasma drug concentrations for several protease inhibitors (PIs) [1][2][3] but not for NNRTIs [3,4], suggesting that plasma concentration could constitute a valid parameter for the TDM of PIs but not, or at least less accurately, for NNRTIs. Direct measurement of intracellular drug concentrations may therefore contribute to improve and adjust antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%